An IoT-Based Model for Monitoring Plant Growth in Greenhouses - Abdool Qaiyum Mohabuth; Devashish Nem (Journal of Information System and Informatics, 2023)
The unstable climatic conditions are promoting the adoption of smart agriculture. The introduction of IoT technology in the cultivation process allows for the monitoring and control of plant growth through automation. While the traditional greenhouse system is already an upgrade to the traditional cultivation system, it still has room for improvement with the integration of technology. The traditional greenhouse system requires close monitoring of growth rates through manual intervention and can be prone to various hazards. Incorrect interpretations of plant requirements can result in wrong interventions that may severely affect plant growth. It is imperative to have accurate data to maintain the health of plants throughout the cultivation process. IoT plays a predominant role in providing accurate data for constant monitoring of plant growth. The aim of this paper is to present a fully functional greenhouse automation model using microcontrollers, sensors, fans, pumps, and appropriate networking routing technology capable of providing instant data for proper monitoring of plant growth. The presented model includes safety features and can issue alerts in case security measures are breached. The system may even allow users to perform remote monitoring using a web application. Therefore, the proposed model will contribute to enhancing the horticultural industry by increasing output and reducing the need for human intervention.